2018
DOI: 10.1016/j.trf.2018.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mental demands on situation awareness during platooning: A driving simulator study

Abstract: Previous research shows that drivers of automated vehicles are likely to engage in visually demanding tasks, causing impaired situation awareness. How mental task demands affect situation awareness is less clear. In a driving simulator experiment, 33 participants completed three 40-min runs in an automated platoon, each run with a different level of mental task demands. Results showed that high task demands (i.e., performing a 2-back task, a working memory task in which participants had to recall a letter, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Fig. 8 provides a comparison between the results of the current on-road study and two previous driving simulator studies (Heikoop et al, 2017;Heikoop, De Winter, Van Arem, & Stanton, 2018). The two simulator studies are similar to the current study as all three studies involved car following in an automated car, drives of 30-40 min duration, identical ECG equipment, and a secondary button-pressing task (detecting bridges in the present on-road study, detecting red cars in the simulator studies).…”
Section: Discussionmentioning
confidence: 61%
“…Fig. 8 provides a comparison between the results of the current on-road study and two previous driving simulator studies (Heikoop et al, 2017;Heikoop, De Winter, Van Arem, & Stanton, 2018). The two simulator studies are similar to the current study as all three studies involved car following in an automated car, drives of 30-40 min duration, identical ECG equipment, and a secondary button-pressing task (detecting bridges in the present on-road study, detecting red cars in the simulator studies).…”
Section: Discussionmentioning
confidence: 61%
“…People tend to produce highly different mental models of AVs (not always correct or comprehensive), and gradually add concepts and links as they experience journeys [84]. It is possible to design procedures that encourage appropriate trust, for example, communicating to users the system capabilities and limitations beforehand [12].…”
Section: Suggestionsmentioning
confidence: 99%
“…Jenness et al (2008) in a survey among early adopters of in-vehicle technology found that system owners often do not understand the limitations of the systems and manufacturers' warnings. Heikoop et al (2018) concluded that mental models ' … are not self-correcting, but rather become increasingly complex with time', suggesting that if drivers don't receive prior information or training on the automated driving system they use, they could retain an inaccurate mental model. 3.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a review of earlier studies, Stanton et al (2001) conclude that 'loss of situational awareness is correlated with poor system performance' and 'people who have lost situational awareness may be slower to detect problems with the system they are controlling as well as requiring additional time to diagnose problems and conduct remedial activities when they are finally detected ' (p.199). Heikoop et al (2018) in a driving simulator study, investigated the impact of a mental secondary task on driver situation awareness during platoon driving and found that mental demand impaired situation awareness. Based on a meta-analysis and narrative review of simulator and on-road studies, de Winter et al (2014) concluded that highly automated driving can improve situation awareness compared to manual driving if drivers are motivated or instructed to detect objects in the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation